ANALISIS SUMBER PENGETAHUAN PEMANFAATAN TUMBUHAN BERPOTENSI PANGAN PADA SUKU DAYAK TAMAMBALOH - Markus Iyus Supiandi; Leliavia Leliavia (LP4MK STKIP PGRI Lubuklinggau, 2019)
The Dayak Tamambaloh tribe in West Kalimantan has local wisdom in utilizing plants that have food potential. However, knowledge of the use of plants with potential food is conveyed through verbal communication, has not been well documented, and parents who have knowledge of food plants have diminished. Therefore, knowledge of sources of knowledge of food crops is very important documented as an effort to preserve cultural heritage. This study aims to analyze the source of knowledge in utilizing food plants in the Dayak Tamambaloh tribal community. The method used in this study was a survey. Research data were obtained through interviews and literature. Data analysis using descriptive qualitative with stages: (a) data collection, (b) data reduction, (c) data presentation, (d) conclusion drawing. The results showed that the source of knowledge in utilizing plants with potential food for the Dayak Tamambaloh tribe was obtained through family, customary leaders, life experiences and trial and error.